2016
DOI: 10.1159/000449483
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interictal Epileptiform Discharges with Sleep and Anti-Epileptic Drugs

Abstract: Background: The presence of interictal epileptiform discharges (IEDs) in electroencephalogram (EEG) is diagnostic of epilepsy. Latent IEDs are activated during sleep. Anti-epileptic drugs (AEDs) improve sleep. AEDs, sleep, and IEDs may interact and affect epilepsy management. Purpose: To explore the occurrence of IEDs and its association with sleep and AED status in suspected patients of epilepsy. Methods: EEG records were collected of suspected patients of epilepsy who reported to the electrophysiology labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They showed VPA superior to Phenobarbital in suppressing interictal epileptiform activity, including both focal and generalized epileptiform activity. Other report described AEDs improve sleep architecture, decrease sleep latency and nocturnal awakening which indirectly may modify interictal EEG abnormalities 33 . Spencer et al 34 confirmed a small but significant decrease in interictal discharges by AED withdrawal.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…They showed VPA superior to Phenobarbital in suppressing interictal epileptiform activity, including both focal and generalized epileptiform activity. Other report described AEDs improve sleep architecture, decrease sleep latency and nocturnal awakening which indirectly may modify interictal EEG abnormalities 33 . Spencer et al 34 confirmed a small but significant decrease in interictal discharges by AED withdrawal.…”
Section: Discussionmentioning
confidence: 93%
“…Other report described AEDs improve sleep architecture, decrease sleep latency and nocturnal awakening which indirectly may modify interictal EEG abnormalities. 33 Spencer et al 34 confirmed a small but significant decrease in interictal discharges by AED withdrawal. Another study reported some AEDs could abolish ictal epileptiform discharge in vitro, but that was unable to block interictal activity on EEG.…”
Section: Discussionmentioning
confidence: 96%
“…Another factor influencing the quality and quantity of sleep is anti-epileptic drugs (AEDs), and their effect differs depending on the patient [25,28,29]. What is certain, however, is that seizures affect the amount and quality of sleep, and sleep affects the frequency of seizures.…”
Section: Introductionmentioning
confidence: 99%
“…Common IEDs are interictal spikes (<70 msec duration) and sharp waves epileptiform discharges (70-200 msec duration). It is commonly accepted that increasing frequency of IEDs are associated with increased risk of seizures in patients with epilepsy [4].…”
Section: Introductionmentioning
confidence: 99%